Pendampingan UMKM dalam Pembuatan Kemasan Produk dan Perizinan Usaha Anggota KUBE Griya Cendekia Sedayu Bantul: Indonesia - Ruchba, Sarastri Mumpuni; Muhlison, Muhammad Bakr (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Griya Cendekia Sedayu is one of the community empowerment centers of the Islamic University of Indonesia (UII) Waqf Foundation (YBW UII). The empowerment program covers various areas, including religious affairs, health, and the productive economy, including agriculture, savings and loans, and Joint Business Groups (KUBE). This community service program focuses on developing Joint Business Group products, aiming to increase sales of fried peanuts from the Griya Cendekia Sedayu Joint Business Group's Micro, Small, and Medium Enterprises (MSMEs). The program includes assistance in product packaging and business licensing for fried peanut products. The methods and stages of implementation of the activities carried out include socialization, assistance in making product packaging and business licensing. This community service program resulted in the creation of a logo and product packaging, as well as business permits in the form of a Business Identification Number (NIB), a Halal Certificate, and a Home Industry Food Production Certificate (SPPIRT) for fried peanut products. As a result of this community service program, Griya Cendekia Sedayu's KUBE fried peanuts, which were initially produced only upon order, have now begun regular production for consignment sales in grocery stores in Bantul and the surrounding areas.